(untitled) - Trịnh, Khắc Thái (Cần Thơ, 2011)
The research aims to find out Confucian ethical thoughts and teaching manifesting in Vietnamese learners’ English argumentative writing and its impact on their argumentative essays
Keywords: Study and teaching,Ngôn ngữ tiếng Anh,Dạy và học,English language; Foreign speakers,English language,Dạy và học,Nguời nói tiếng nước ngoài,Ngôn ngữ tiếng Anh,Studying and teaching